Soil Science and Soil Terminology in Uzbek and English (European Science Methodical Journal, 2023)
Soil science involves the study of the formation and distribution of soil, the biological, chemical and physical properties and processes of soil and how these processes interact with wider systems to help inform environmental management, industry and sustainable development.